EVALUATION OF THE ECONOMIC EFFICIENCY OF AGROINDUSTRIAL CLUSTERS IN SAMARKAND REGION (Scientific journal of the Fergana State University, 2025)
This article covers the economic indicators, areas of activity, achieved productivity and employment of agro-industrial clusters in Samarkand region. Also, the level of technical efficiency, that is, the conversion of resources into income, was analyzed using data coverage analysis of the largest cotton-textile clusters in the region: “Afrosiyob Jeans Textile” and “Samarkand Kamalak Invest Textile”.